Astroblastoma (Pulse, 2011)
Aims and Objectives: Astroblastoma is one of the very unusual type of brain tumours, whose histogenesis has not been clarified. It occurs mainly among children and young adults. Astroblastoma has characteristic histological picture and varied biological behavioural. We report a 10-year old girl diagnosed as a case of astroblastoma.Clinical presentation: A 10-year old girl was examined for intermittent frontal headache and convulsion for two years. MRI revealed brain tumour which was later confirmed as astroblastoma by histopathological examination.Conclusion: Astroblastoma is rare because of its varied biological behaviour.DOI: http://dx.doi.org/10.3329/pulse.v4i1.6966Pulse Vol.4 January 2010 p.38-39